FV 4. Contribution of Wada test results to the prediction of change in verbal learning and memory function after epilepsy surgery in the temporal lobe. Issue 8 (August 2021) - Conradi, N.; Rosenberg, F.; Knake, S.; Biermann, L.; Haag, A.; Gorny, I.; Hermsen, A.; von Podewils, V.; Behrens, M.; Gurschi, M.; du Mesnil de Rochemont, R.; Menzler, K.; et al.
Abstract : Introduction . Although the Wada test was initially established as the gold standard for determining hemispheric language and memory lateralization, in recent years its application in the presurgical evaluation of epilepsy surgery candidates has decreased due to the development of noninvasive alternatives [1]. While some studies questioned the predictive value of Wada test results for possible postsurgical cognitive impairment, others supported its usefulness [2]. Thus, this study was designed to contribute to the solution of this issue continuously debated among researchers in the field. Methods. Data from 56 patients with temporal lobe epilepsy who received Wada tests and underwent epilepsy surgery was analyzed retrospectively. Pre- and postsurgical verbal learning and memory function was assessed using a standard neuropsychological test battery. Hierarchical linear regression analyses were performed to determine the incremental value of Wada test results over socio-demographic, clinical, and neuropsychological characteristics in predicting postsurgical change in verbal learning and memory function. Results. Adding Wada test results significantly improved the prediction models of postsurgical change in verbal learning function ( ΔR2  = 0.291, p  = .028), and postsurgical change in verbal memory function ( ΔR2  = 0.373, p  = .001). Presurgical performance, age, and Wada scores accounted for 47.8% of variance in postsurgical change in verbal learning function, and 61.0% of variance in postsurgical change in verbal memory function. Discussion. Our findings confirm that Wada test results are of significant incremental value for the prediction of postsurgical change in verbal learning and memory function. Thus, the Wada test contributes to balancing out the risks and benefits of epilepsy surgery, and therefore remains an important part of the presurgical work-up of selected patients with clear indications. [1] Baxendale, S., Thompson, P. J., & Duncan, J. S. (2008). The role of the Wada test in the surgical treatment of temporal lobe epilepsy: an international survey. Epilepsia, 49 (4), 715-720. [2] Parra-Díaz, P., & García-Casares, N. (2019). Memory assessment in patients with temporal lobe epilepsy to predict memory impairment after surgery: A systematic review. Neurología (English Edition), 34 (9), 596-606.